Progression of white matter hyperintensities and incidence of new lacunes over a 3-year period: the leukoaraiosis and disability study - Gouw, Alida A.; Flier, Wiesje M. van der; Fazekas, Franz; Straaten, Elisabeth C. W. van; Pantoni, Leonardo; Poggesi, Anna; Inzitari, Domenico; Erkinjuntti, Timo; Wahlund, Lars O.; Waldemar, Gunhild; Schmidt, Reinhold; Scheltens, Philip; et al. (Stroke, 2008)
Background and Purpose: We studied the natural course of white matter hyperintensities (WMH) and lacunes, the main MRI representatives of small vessel disease, over time and evaluated possible predictors for their development.Methods— Baseline and repeat MRI (3-year follow-up) were collected within the multicenter, multinational Leukoaraiosis and Disability study (n=396). Baseline WMH were scored on MRI by the Fazekas scale and the Scheltens scale. WMH progression was assessed using the modified Rotterdam Progression scale (absence/presence of progression in 9 brain regions). Baseline and new lacunes were counted per region. WMH and lacunes at baseline and vascular risk factors were evaluated as predictors of WMH progression and new lacunes.Results— WMH progressed (mean±SD=1.9±1.8) mostly in the subcortical white matter, where WMH was also most prevalent at baseline. The majority of new lacunes, which were found in 19% of the subjects (maximum=9), also appeared in the subcortical white matter, mainly of the frontal lobes, whereas most baseline lacunes were located in the basal ganglia. Baseline WMH and lacunes predicted both WMH progression and new lacunes. Furthermore, previous stroke, diabetes, and blood glucose were risk factors for WMH progression. Male sex, hypertension, systolic blood pressure, previous stroke, body mass index, high-density lipoprotein, and triglyceride levels were risk factors for new lacunes.Conclusion— WMH and lacunes progressed over time, predominantly in the subcortical white matter. Progression was observed especially in subjects with considerable WMH and lacunes at baseline. Moreover, the presence of vascular risk factors at baseline predicted WMH progression and new lacunes over a 3-year period.
Gesehen am 26.03.2021
Participating center and personnel: Timo Erkinjuntti, MD, PhD, Michael Hennerici, MD, Christian Blahak, MD, Hansjorg Baezner, MD und weitere